From allies to neighbours: Unravelling the impact of foreign military presence on local communities in Poland - Smułek, Grzegorz (Quaestiones Geographicae, 2026)
This article analyses the multifaceted impact of foreign military presence (FMP) on local communities in Poland, with a particular focus on the broader social, economic, and environmental consequences of foreign military bases (FMBs). Grounded in an interdisciplinary theoretical framework drawing on concepts from regional development, behavioural geography, and sociology, the study explores how the presence of NATO forces transforms local spaces and civil-military relations in a post-socialist country. Employing a mixed-methods approach that integrates both qualitative and quantitative techniques and draws on diverse data analysis methods, the article examines four locations hosting foreign military infrastructure. The findings reveal a complex and context-dependent picture of FMB impacts on local communities which report numerous social and economic benefits while also expressing concerns related to environmental degradation, infrastructural burdens, and perceived security risks. Public attitudes towards FMP are shaped by a range of socio-demographic and contextual factors, including the previously rotational nature of troop deployments, which has hindered the development of long-term integration. The study also highlights a discrepancy in social attitudes between local leaders and residents. The article concludes with recommendations aimed at enhancing civil-military cooperation and supporting more sustainable and inclusive local development strategies. It also outlines directions for future research, particularly comparative studies in other regions experiencing intensified foreign military engagement.